Diachronic dynamics of Middle English phonotactics provide evidence for analogy effects among lexical and morphonotactic consonant clusters - Baumann, Andreas; Ritt, Nikolaus; Prömer, Christina (Papers in Historical Phonology, 2016)
Consonant clusters that rarely occur lexically (i.e. within morphemes) may function as complexity markers when they span a morpheme boundary, i.e. when they occur morphonotactically. In this study we observe patterns in the diachronic dynamics of Middle English which hint at mutually beneficial effects between morphonotactic and lexical clusters. We suggest that the patterns revealed can be explained by frequency-based analogy effects in language acquisition.